THE ANALYSIS OF CUSTOMER PURCHASE INTENTION OF HOUSES USING REAL ESTATE AGENT IN MANADO BASED ON PSYCHOLOGICAL FACTORS - Ticoalu, Vinny O. (Sam Ratulangi University, 2016)
ABSTRACT Real estate agent business field becomes a trend nowadays. Real estate agent helped customers to buy or sell a house. Psychological factors has an influence in real estate agent busniess, customers mostly asked the opinion from others about the real estate agent in case they do not want to choose a wrong real estate agent. This research aims to analyze the influence of psychological factors on customers purchase intention in using real estate agent in Manado. This research used a multiple linear regression analysis with the sample is 75 respondentds that were obtained from adult citizen in Manado. The result show perception and learning have significant influences to customer purchase intention to using the real estate agent. Motivation, attitude and belief is not significantly influence. Otherâ€™s perception is really affected customer mind to choose real estate agent. Customers like to getting knowÂ about real estate agent to buying a house. Keywords : Psychological Factor, Customer Purchase Intention